PENGARUH KEPEMIMPINAN KEPALA SEKOLAH BERBASIS TRI HITA KARANA TERHADAP KINERJA GURU - Budiarti, Luh Putu Yudha; Ida Bagus Putu Arnyana; Ketut Suma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze and empirically prove the effect of Tri Hita Karana-based principal leadership on teacher performance in elementary schools across Cluster 4 Taro, Tegallalang District. This study used a quantitative approach with a correlational ex-post facto research design. The population in this study consisted of 50 teachers. Data collection was carried out using a closed-ended Likert scale questionnaire that had met the validity and reliability test criteria. The collected data were analyzed using classical assumption tests and simple linear regression analysis assisted by IBM SPSS Statistics 26 software. The results showed that Tri Hita Karana-based principal leadership had a positive and significant effect on teacher performance. This is evidenced by a t-test significance value of 0.000 < 0.05 and a t-count value of 18.357, which is greater than the t-table of 2.011. The regression equation formed is Y = 2.248 + 0.969X. The coefficient of determination (R Square) value of 0.875 indicates that 87.5% of the variation in teacher performance can be explained by Tri Hita Karana-based leadership, while the remaining 12.5% is influenced by other factors outside the model. In conclusion, the implementation of Parahyangan, Pawongan, and Palemahan values by the principal is proven to be essential in building a harmonious work ecosystem and is able to improve educators' professionalism.